1977
DOI: 10.1128/iai.16.3.754-759.1977
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus glycoprotein. II. Biological and serological characterization

Abstract: Purified rabies virus glycoprotein (G) was shown by complement fixation and immunodiffusion tests to be a second distinct antigen of the virus. It it the only structural protein of the virus that induces the formation of virus-neutralizing antibodies and which confers immunity to animals. When the G protein is taken as antigen, the complement fixation test can be used for the assay of virus-neutralizing antibodies. The total protective activity of the virus was recovered in the purified G protein preparation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(80 citation statements)
references
References 18 publications
1
73
0
6
Order By: Relevance
“…These facts indicate the need of more faithful candidate vaccines which must be capable of inducing strong immune response to protect from infection. More importantly, the candidate immunogen must be able to induce a strong Th2 immunity as it has been established that Th2; that is, the humoral immune response plays a predominant role in induction of protective immunity against rabies virus [32][33][34]. Rabies virus glycoprotein is the main antigen responsible for inducing the production of rabies virus-neutralizing antibodies and for conferring immunity against lethal rabies infection.…”
Section: Discussionmentioning
confidence: 99%
“…These facts indicate the need of more faithful candidate vaccines which must be capable of inducing strong immune response to protect from infection. More importantly, the candidate immunogen must be able to induce a strong Th2 immunity as it has been established that Th2; that is, the humoral immune response plays a predominant role in induction of protective immunity against rabies virus [32][33][34]. Rabies virus glycoprotein is the main antigen responsible for inducing the production of rabies virus-neutralizing antibodies and for conferring immunity against lethal rabies infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that rabies virus G protein could be isolated from Triton X-100-disrupted rabies virus, without losing its biological and serological properties (Atanasiu et al, 1974(Atanasiu et al, , 1976Cox et al, 1977;Smith et al, 2006). In this study, the inactivated rabies virus was purified by sucrose gradient centrifugation, then soluble glycoprotein was dissociated from the virus by incubation with 1% Triton X-100 and purified by sucrose centrifugation and Sephadex G-50 filtration.…”
Section: Purification Of Rabv G Proteinmentioning
confidence: 74%
“…Rabies virus glycoprotein is the only structural protein of the virus that induces the formation of virus-neutralizing antibodies, which confer immunity to animals. The protective activity was shown to be associated only with the G protein and not with the membrane associated protein M and P, although they contain residual traces of G protein (Cox et al, 1977). Competitive ELISA that utilizes a cell line stably expressing the rabies virus G protein as the coating antigen has higher specificity and sensitivity than that of ELISA based on whole rabies virus antigen (Bahloul et al, 2005;Servat and Cliquet, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations